Social relationships and their impact on health-related quality of life in a long-term breast cancer survivor cohort - Belau, Matthias; Jung, Lisa; Maurer, Tabea; Obi, Nadia; Behrens, Sabine; Seibold, Petra Beate; Becher, Heiko; Chang-Claude, Jenny (Cancer, 2024)
Background Health-related quality of life (HRQOL) has become increasingly important for breast cancer survivors, but clinically relevant declines often persist for many years after treatment. This study aimed to investigate whether social relationships can mitigate or prevent this decline in HRQOL. Methods Data were used from the German population-based Mamma Carcinoma Risk Factor Investigation (MARIE) cohort of 2022 breast cancer cases with follow-up information for more than 15 years after diagnosis. Correlations between social integration, social support, and global health status (GHS) as an overall measure of HRQOL were analyzed, and linear regression analysis was performed with structural equation modeling. Results The majority of participants reported high levels of social integration and social support and moderate levels of GHS. Social integration 5 years after diagnosis was associated with GHS 5 years after diagnosis (β = 1.12; 95% CI, 0.25-1.99), but no longitudinal effects were found. Social support 5 years after diagnosis was associated with better GHS 5 years (β = 0.42; 95% CI, 0.36-0.48) and 10 years after diagnosis (β = 0.12; 95% CI, 0.02-0.22), whereas social support 10 years after diagnosis was associated with GHS 10 years (β = 0.29; 95% CI, 0.20-0.39) and 15 years after diagnosis (β = 0.10; 95% CI, 0.01-0.21). Conclusions These results confirm that social relationships positively influence HRQOL in long-term breast cancer survivors and that their association should receive more attention clinically and beyond routine care.
Veröffentlicht: 17 May 2024
Gesehen am 18.11.2024